The role of DNA repair gene inhibition on chronic arsenic-induced liver sinusoidal cells damage - Buyong, Zunariah; Saharudin, Shahida; Talib, Norlelawati A.; Abdullah, Nor Zamzila; Ab Rahman, Jamalludin; Wan Salleh, Wan Muhamad Salahudin; Zulkiflee, Khodijah (2019)
Arsenic is hazardous to health and strongly associated with carcinogenic effects, cardiovascular and liver diseases. Even though organic arsenic is believed to be less dangerous, the postulation is hard to prove since the evidence is still lacking. The World Health Organisation (WHO) permissible limit for the concentration of arsenic in drinking water is currently at 10 μg/L. The long-term effect on low dose exposure is also not established. Inorganic arsenic causes apoptotic and necrotic damage to hepatocytes and capillarization of liver sinusoidal endothelial cells (LSECs), an important preceding event upon exposure. In other cell types, including hepatocytes, inorganic arsenic causes inhibition of DNA repair. However, its effect on the DNA repair system in LSECs is unknown. Therefore, this study aimed to investigate the changes to liver functions, its cellular morphology and selected gene expressions involved in apoptosis and DNA inhibition pathways following chronic low dose organic arsenic exposure. It is hypothesized that this exposure causes changes to cellular morphology such as defenestration in LSECs, which is due to inhibition of DNA repair gene. Sixty Sprague Dawley rats were assigned for either morphology or genetic parameters. The animals were further randomly divided into either control or experimental groups according to observation periods; 2, 4 or 6 months. Experimental groups were exposed for 5 days a week to monosodium methyl arsonate (MSMA) at a concentration of 63.20 mg/kg body weight (actual arsenic content of 7.3 mg) through oral gavage. The liver enzymes were collected before the animal subjected for liver perfusion under anaesthesia with either fixative buffer for morphological study or digestive buffer for genetic study. Aspartate transaminase (AST) levels were not significantly lower than their respective controls (2-month control 213.1 IU/L(SD 76.7); 2-month treated 211.3 IU/L (SD 55.6);4-month control 214.9 IU/L (SD 55.1); 4-month treated 168.0 IU/L (SD 34.8);6-month control 196.7 IU/L (SD 46.6); 6-month treated 180.2 IU/L (SD 45.6) . Alanine aminotransferase (ALT) and alkaline phosphatase (ALP) levels in 4-month groups were significantly lower compared to its controls (p<0.005). ALT (2-month control 87.4 IU/L(SD 21.9); 2-month treated 70.4 IU/L (SD 11.5);4-month control 85.3 IU/L (SD 13.0); 4-month treated 52.0 IU/L (SD 5.2);6-month control 83.7 IU/L (SD 25.3); 6-month treated 62.5 IU/L (SD 16.2). ALP (2-month control 236.9 IU/L(SD 42.1); 2-month treated 193.9 IU/L (SD 72.5);4-month control 237.6 IU/L (SD 52.8); 4-month treated 162.9 IU/L (SD 28.9);6-month control 192.7 IU/L (SD 43.5); 6-month treated 183.0 IU/L (SD 46.5). Control and 2-month groups showed normal morphology. The 4-month treated rats showed cytoplasmic vacuolation, focal necrosis, minimal inflammatory cells and fibrosis. Hepatic cords were disrupted, blebbing and comparatively reduction of fenestrae. More extensive changes in 6-month treated rats and less intense glycogen staining. The number of LSECs isolated ranged from 2.64 to 41.84 x 106 per ml of liver suspension. The mean number of cells isolated from 4-month groups was significantly lower(2-month control 16.74 (SD 11.64); 2-month treated 20.44 (SD 8.56);4-month control 8.12 (SD 1.14); 4-month treated 2.64 (SD 1.01);6-month control 47.80 (SD 8.79); 6-month treated 41.83 (SD 20.52). LSECs gene expressions in the 2-month treated group showed significantly down-regulated cell cycle gene (Tp53), base excision repair gene (Xrcc1) and death domain receptor gene (Tnfrsf1a). While in the 4-month treated group, base excision repair gene (Xrcc1), apoptotic gene (Bax), death domain receptor (Tnfrsf1a) and caspase gene (casp2) were significantly up-regulated. In the 6- month group, only base excision repair (Mpg) was significantly up-regulated by 5 folds.The organic arsenic cause reduction in liver enzymes and increased apoptotic-related gene at sub-chronic exposure but increased DNA repair gene expression at chronic exposure.